2014
DOI: 10.1136/ejhpharm-2014-000491
|View full text |Cite
|
Sign up to set email alerts
|

Hospital pharmacist interventions in a central hospital

Abstract: Objective The aim of this study is to describe and categorise pharmacist interventions (PIs) in a central hospital and report acceptance rates by physicians. Methods A retrospective study was carried out in a 350-bed central hospital between January and June 2013. Eleven pharmacists screened the pharmacotherapy charts for drug-related problems leading to PIs. The recommendations resulting from this analysis were entered in the electronic prescribing system. All the PIs registered on the electronic medical reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
6
6
1
Order By: Relevance
“…This acceptance rate is somewhat higher than the acceptance rate of 62% found in the French multi-centre study referred to in the introduction section [3]. Others have reported even lower acceptance rates of around 50% [6,12,13]. The higher acceptance rate found in our study could perhaps be explained by the accurate assessment of the clinical relevance of potential drug-related problems by our pharmacists, illustrated by the small number of clinically irrelevant alerts.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…This acceptance rate is somewhat higher than the acceptance rate of 62% found in the French multi-centre study referred to in the introduction section [3]. Others have reported even lower acceptance rates of around 50% [6,12,13]. The higher acceptance rate found in our study could perhaps be explained by the accurate assessment of the clinical relevance of potential drug-related problems by our pharmacists, illustrated by the small number of clinically irrelevant alerts.…”
Section: Discussioncontrasting
confidence: 77%
“…This indicates that physicians' decisions to accept interventions generally are based on the discussion with the pharmacist, since they hardly viewed the recorded recommendations. Previous studies indeed have shown that verbally communicated interventions are much more likely to be accepted than interventions that are only recorded electronically [6,25]. These findings support the feasibility and safety of pharmacists located in the hospital pharmacy proposing interventions for drug-related problems over the telephone.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In this study, as in other similar studies,19 the most frequently proposed PI was antimicrobial dose adjustment or interval modification due to kidney dysfunction. In view of these results, and because PIs in patients with chronic kidney conditions seem to have a direct positive impact on patient outcomes,20 we suggest that attending physicians should receive pharmacological training about the dosage for patients with impaired kidney function.…”
Section: Discussionsupporting
confidence: 52%
“…Overall, dose changes contributed to the highest percentage of recorded interventions. This is consistent with several published studies investigating pharmacist interventions in other therapeutic areas [31][32][33][34]. Hence, this demonstrates lack of prescriber familiarity with dosing regimens and necessitates for further prescriber education.…”
Section: Key Ndingssupporting
confidence: 89%